The Frequency and Risk Factors of Acute Kidney Injury in Children with Oncological Diseases: A Single-Center Study in Bulgaria - Petya Markova; Antoniya Yaneva; Stoyan Markov; Mariya Spasova; Neofit Spasov (Children)
Background: Progress in the treatment of childhood oncological diseases has led to the prolonged survival of patients with this severe diagnosis. On the other hand, the prolonged chemotherapy courses that achieve this outcome also bring a number of complications, with acute kidney injury being one of them. Its occurrence in patients not only affects their quality of life but also prolongs and increases the cost of hospitalization, burdens the body with additional treatment, and impacts the ability to manage the underlying disease. Aim: The aim of this study is to determine the frequency of acute kidney injury among children hospitalized in the Pediatric Oncohematology Unit in Plovdiv during the period 2016–2020, as well as to identify the risk factors for its occurrence, its severity, and its dependence on tumor type, gender, and age. Patients and Methods: During the five-year period under review, a total of 213 newly diagnosed children with hematological diseases were admitted to our Pediatric Oncohematology Unit—122 boys and 91 girls. Results: Acute kidney injury was identified in 94 (44.1%) of the children—54 with solid tumors and 40 with malignant hemopathies. The main cause of acute kidney injury diagnosed was drug-induced nephrotoxicity, especially due to nephrotoxic chemotherapeutic agents. No statistically significant association was found between the type of tumor and the occurrence of acute kidney injury. Of the children with documented episodes of AKI, 11 were found to have CKD according to the KDIGO criteria. Conclusions: Acute kidney injury is a common complication that occurs during the medical treatment of children with malignant diseases.